MAP OF CRIME RATE VULNERABILITY ON JAVA ISLAND - I Wayan Tedy Setiawan; Ni Luh Putu Suciptawati; I Made Eka Dwipayana (INJOSEDU: International Journal of Social and Education, 2025)
The level of vulnerability to crime in Indonesia remains high, thus effective preventive measures and collaboration from various parties are necessary to create a safer and more orderly environment. According to the Central Statistics Agency in 2022 the number of crimes in Indonesia in 2022 experienced a significant increase from the previous year. Based on Criminal Statistics in 2022 the number of crimes for the police level during 2022 Java Island occupies the top place in the crime rate in Indonesia. Countermeasures related to crime can be done by knowing the areas prone to crime. This study uses analytical methods that can show spatial autocorrelation, including the Moran Index and Local indicators of spatial association (LISA). The results show that there is spatial autocorrelation with a clustered pattern for the crime rate on the island of Java and districts / cities in Java which are classified as crime-prone / hotspot areas, namely Bogor, Gresik, West Jakarta, Central Jakarta, South Jakarta, East Jakarta, North Jakarta, Bekasi City, Depok City, Tanggerang City, South Tanggerang City, and Sidoarjo.